Impact of Public Spending on the Quality of Life in Rural Bangladesh - Fardoush, Zannatul (Advances in Social Sciences Research Journal, 2020)
Public spending is one of the most effective instruments in improving the quality of life as an entrenched goal of economic development. However, as the resources are limited, a better distribution would, therefore, require a thorough investigation regarding the impact analysis of public spending on actual development factors. This paper has examined the link between public expenditures in different sectors of economy and improvement in the quality of life through the channel of agricultural growth or rural development in Bangladesh and also throughs the education channel such as the school enrollments. A simultaneous equation model in the form of a 3-Stage Least Square (3SLS) technique has been used to explore the impacts of public spending. By using the data from 1982-2017, this study finds that public spending in education, health, social safety net, and agriculture has positive impacts on the quality of life advancement. A 1 percent increase in public spending in education would result in an increase in quality of life (proxied by life expectancy) by 0.182 percent on average, ceteris paribus. The public expenditure elasticities in health, social safety net, and agriculture on the quality of life are found as 0.05, 0.03, 0.04 respectively. The only concern is the spending in the transportation and communication sector which is probably due to the misallocation and mismanagement of available resources and funds into this sector. Hence, to grasp the agricultural and rural development, the government should continue to institutionalize the policies that support the education of the poor in rural areas.